The Correlation between Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) and Insulin Resistance and the Components of Atherogenic Lipoprotein Phenotype in Males with Central Obesity - Yusmiati Yusmiati; Burhanuddin Bahar; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2010)
BACKGROUND: Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) promotes the degradation of LDL receptor in hepatocytes. in vitro studies have proven that insulin increases the expression of PCSK9. Insulin resistance, a common condition in central obesity is characterized by dyslipidemia called Atherogenic Lipoprotein Phenotype (ALP). This study aimed to investigate the correlation between insulin resistance (HOMA-IR) and PCSK9, and to analyze whether this condition is related to the development of ALP in central obesity.METHODS: This is an observational study with crosssectional design. The subjects consisted of 62 male adults with central obesity, aged 30-60 years old. ELISA was used to measure plasma PSCK9.RESULTS: The mean plasma PCSK9 concentration of the samples was 283.7 ng/mL. PCSK9 had positive linear correlation with HOMA-IR (r=0.225, p=0.045) and Apo B (r=0.245, p=0.055). After controlling of HOMA-IR, PCSK9 had positive linear correlation with triglycerides (r=0.352, p=0.045). In population with HOMA-IR >2, crosstabs analysis showed that PCSK9 had significant correlation with triglycerides and Apo B with an odd ratio of 6,125 (r=0.376, p=0.037). Triglyceride showed significant negative correlation with HDL cholesterol and ratio of LDL/Apo B, but neither HOMA-IR nor PCSK9 did.CONCLUSION: In males with central obesity, PCSK9 is one of the factors mediating the occurence of ALP in insulin resistance.KEYWORDS: PCSK9, insulin resistance, atherogenic lipoprotein phenotype